LARVICIDAL ACTIVITY OF INVASIVE WEEDS CASSIA UNIFLORA AND SYNEDRELLA NODIFLORA - NIVEDITA GHAYAL; ANAND PADHYE; KONDIRAM DHUMAL (International Journal of Pharma and Bio Sciences, 2010)
Cassia uniflora and Synedrella nodiflora are the dominant invasive weeds in the campus of Pune University (M.S.) India. Their allelopathic activity has greatly affected the phytodiversity in the campus. With the view of their huge biomass prospecting, the larvicidal potential of aqueous leaf leachates of these weed species were tested against the larvae of Aedes aegypti. The experiments revealed that leaf leachates of both the weeds showed lethal effects on the larvae. The effect of Synedrella nodiflora leaf leachates was more pronounced than that of Cassia uniflora. The mortality was observed to increase with increasing exposure and the concentrations of leaf leachates of both the weeds. This larvicidal activity was probably due to the presence of allelochemicals present in the leaf leachates of these two plants. HPTLC was used to analyze these allelochemicals, which revealed that the leaves of both the plants were containing terpenoids, steroids, flavonoids and pungent and bitter essential oils.